A comparison of local and systemic acyclovir in the management of herpetic disciform keratitis. Issue 5 (May 1990) - Porter, S. M.; Patterson, A.; Kho, P.
Abstract : Forty-three patients with active herpetic disciform keratitis were entered into an open study to compare the efficacy of oral acyclovir (400 mg) with acyclovir ophthalmic ointment (3%) to inhibit viral replication during treatment with 0.05% prednisolone eye drops. All patients, regardless of the mode of therapy, were treated five times a day until they were healed. The mean time to heal in the oral group was 25.9 days and in the topical group was 25.3 days. Resolution of lacrimation was significantly faster in the oral group (12.1 days versus 27.6 days). The patients on tablets also showed a greater improvement in visual acuity. No statistically significant differences were found between the two groups in the incidence of recurrences over a three-year post-treatment period. It is concluded that oral acyclovir treatment is an effective alternative to ophthalmic ointment in the management of herpetic disciform keratitis.